Effectiveness of the SIMPADA System in Regional Entertainment Tax Administration: Evidence from UPTB 5 Bapenda Surabaya - Nasywa Salsabiila; Sri Trisnaningsih (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2026)
The progressive integration of information technology into sub-national governance has prompted numerous Indonesian local authorities to transition toward digital platforms for more systematic revenue administration. This study investigates how SIMPADA (Sistem Informasi Manajemen Pendapatan Daerah Regional Revenue Management Information System) performs in the administration of entertainment tax in the city of Surabaya, with concentrated attention on operational activities at Unit Pelaksana Teknis Badan (UPTB) 5 Regional Revenue Management. The investigation was conducted across an internship period at UPTB 5, Badan Pendapatan Daerah (Bapenda) Surabaya, spanning approximately six months. Primary data originated from a structured Likert-scale questionnaire administered to 30 tax administration personnel actively engaged with SIMPADA, supplemented by secondary data on entertainment tax revenue figures and taxpayer compliance statistics drawn from official Bapenda Surabaya records. Analysis applied descriptive statistical procedures encompassing frequency distribution, mean score computation, and percentage assessments across input, process, and output effectiveness dimensions. Results demonstrate that SIMPADA has generated tangible improvements to the efficiency and precision of entertainment tax administration, with the process dimension recording the highest mean effectiveness score. Nonetheless, recurring challenges include incomplete taxpayer database coverage and limited tax awareness among entertainment business operators. The quantitative evidence affirms SIMPADA's overall effectiveness and provides an empirical basis for advancing regional entertainment tax governance and digital tax policy in Indonesian local government settings.